Latin America and Caribbean environment outlook (UNEP Colonia Lomas VirreyesMX, 2000)
Looks at the state of the environment. Analyses the main response policies of Latin American and Caribbean countries at the international, regional (or sub-regional) and national levels.
Keywords: ENVIRONMENT